Image Repair and Crisis Communication Strategies in YouTuber Apologies and the Varying Public Reactions : The Power of Words When Being Exposed and Canceled - Ervasti, Mari (My University, 2022)
The main purpose of this comparative study is to find out how many and what kind of image repair strategies are used in three select YouTuber apology videos and what kind of responses they received from the public. The chosen videos are “My apology” by Laura Lee (2018), “Tati” by James Charles (2019), and “Doing What’s Right” by Jeffree Star (2020). Additionally, I intend to find out how the image repair strategies correlate with the audience responses to the apology, as well as what kind of power relations, social significance, and marketing aspects are associated with the apology video phenomenon and cancel culture specifically in this case. The study utilizes an integrated image repair strategy framework based on William Benoit’s Image Repair Theory and Timothy Coombs’ Crisis-Response Strategies originally assembled by Heikkinen in her 2020 University of Turku MA thesis on image repair strategies and theme structure in aerospace giant Boeing’s press releases. The analysis of the response from the audience is conducted by using the advanced search function on Twitter and close reading 300 tweets in total. The study is both qualitative and quantitative. The image repair analysis revealed that there were 89 image repair strategy occurrences throughout all three apology videos. Of the 89 occurrences, 27 were in Lee’s video, 19 in Charles’ video, and 43 in Star’s video. Ingratiation and mortification strategies were the most commonly used image repair strategies throughout all three apologies. Star’s apology was the most diverse in terms of image repair strategy choices out of the three videos. Ingratiation was the largest category in both Charles’ and Star’s videos, with mortification as the runner-up. The largest category in Lee’s video was mortification, and the second spot was shared between ingratiation and suffering strategy. The least popular strategy overall was denial. In terms of the subtypes of image repair strategies, all three apology videos had simple mortification as their most commonly used subtype. Praising others, bolstering and the suffering strategy were also quite commonly used throughout the three videos. All three videos received immensely negative reactions from the audience – even Star’s video, which appeared to be the best-received, got 90 negative, five neutral and five positive assessments out of a hundred. Charles’ video was the worst-received, though there were only minor differences. According to the results, there seems to be a pattern – the less image repair strategy occurrences, the worse the reception from the audience. Utilizing a diverse array of image repair strategies seems to also affect the audience’s reaction positively. Additionally, recent YouTuber apologies seem to be part of a calculated marketing strategy more so than older ones. Using these strategies seems to be an attempt to have at least some power over the “cancel culture” phenomenon in which the audience is usually in control. Nevertheless, it is clear that more research is needed to uncover these causal connections in more detail. Especially the responses from the audience can, at most, be considered as indicative of a larger phenomenon that requires more research.
Keywords: apologies, image repair, Image Repair Theory, crisis communication, Crisis-Response Strategies, social media, YouTube, cancel culture